Structure and immunomodulatory activity of Lentinus edodes polysaccharides modified by probiotic fermentation - Jingjing Liang; Meina Zhang; Xiaohan Li; Yuan Yue; Xiaowei Wang; Mengzhen Han; Tianli Yue; Zhouli Wang; Zhenpeng Gao (Food Science and Human Wellness)
Plant-based fermentations provide an untapped source for novel biotechnological applications. In this study, a probiotic named Lactobacillus fermentum 21828 was introduced to ferment Lentinus edodes. Polysaccharides were extracted from fermented and non-fermented L. edodes and purified via DEAE-52 and Sephadex G-100. The components designated F-LEP-2a and NF-LEP-2a were analyzed by FT-IR, HPGPC, HPAEC, SEM, GC-MS and NMR. The results revealed that probiotic fermentation increased the molecular weight from 1.16 × 104 Da to 1.87 × 104 Da and altered the proportions of glucose, galactose and mannose, in which glucose increased from 45.94 % to 48.16 %. Methylation analysis and NMR spectra indicated that F-LEP-2a and NF-LEP-2a had similar linkage patterns. Furthermore, their immunomodulatory activities were evaluated with immunosuppressive mice. NF-LEP and F-LEP improved immune organ indices, immunoglobulin (IgG and IgM) and cytokines concentrations; restored the antioxidation capacity of liver; and maintained the balance of gut microbiota. F-LEP displayed better moderating effects on the spleen index, immunoglobulin, cytokines and the diversity of gut microbiota than NF-LEP (200, 400 mg/kg). Our study provides an efficient and environment-friendly way for the structural modification of polysaccharides, which helps to enhance their biological activity and promote their wide application in food, medicine and other fields.